Comparative study of adsorptive role of carbonaceous materials in removal of UV-active impurities of paclitaxel extracts - Jaber Nasiri; Elaheh Motamedi; Mohammad Reza Naghavi (Elsevier, 2015)
Graphite oxide (GO) and reduced graphene oxide (rGO) nanosheets were synthesized with a low-cost manufacturing method. The morphology and structures of the synthesized samples were studied using X-ray diffraction (XRD), atomic force microscopy (AFM), Fourier-transform infrared (FTIR) and Raman spectroscopy. The efficiencies of GO and rGO as novel candidate adsorbents in the pre-purification of paclitaxel were compared and contrasted with those of commercial graphite (Gt), graphene (G) and multi-wall carbon nanotube (MWCNT). According to UV-vis and HPLC analyses, rGO was evaluated as the best absorbent for the removal of impurities in pre-purification of paclitaxel from plant cell cultures. In contrast, the GO had the poorest proficiency for paclitaxel pre-purification in comparison with the other carbonaceous adsorbents. This is attributed to the existence of many localized defects in the π-structure of GO that is related to weakness of π-π stacking interactions between crude extract impurities and GO.